Toward sustainable solar energy: Analyzing key parameters in photovoltaic systems - Nugzar Gomidze; Lali Kalandadze; Omar Nakashide; Izolda Jabnidze; Miranda Khajishvili; Jaba Shainidze (AIP Advances)
This study reviews recent advancements in solar energy technologies, focusing on enhancing the efficiency of photovoltaic systems. Key research areas include optimizing material properties, improving charge separation, and addressing sustainability challenges. This study identifies critical challenges in quantum dot solar cell technology, such as modeling spectral absorption, managing thermal losses, and evaluating long-term stability. Overall, these innovations represent significant strides toward more efficient and environmentally friendly solar energy solutions. This Review article offers a thorough investigation of the direct current parameters in photovoltaic panels, aiming to boost their efficiency and cost-effectiveness in production. This study underscores the importance of precise modeling and identification of solar cell parameters to more effectively harness solar energy, thereby underscoring its potential for enhancing energy capacity and environmental conservation. Our research includes experimental data on polycrystalline silicon solar cells and simulation results of both individual and polycrystalline cells conducted using the NI Multisim simulator. The focal points of this study encompass the efficient use of solar energy, the pivotal role of silicon as a semiconductor material, and novel methods for augmenting photovoltaic cell efficiency, such as employing nanowires and multilayer semiconductors. This Review Article also examines the effect of temperature on solar cell efficiency and addresses both the theoretical and practical measures of key photovoltaic parameters, including short-circuit current, open-circuit voltage, fill factor, and conversion efficiency.